An Empirical Analysis of the Determinants of Cost Efficiency: Evidence from China - Liu, Aode (2019)
During the period of 2013-2018, China gradually experienced a growth in economics and finance, especially in the banking sector. This paper examines 100 commercial banks in China during 2013-2018, covering 5 ownership structures within 6 administrative area. The purpose of this study is to find out the determinants that are influential to cost efficiency and the correlations with efficiency. By comparing the means, the standard derivations and the correlations, it was eventually concluded that the joint-stock commercial banks seem to be more efficient compared with state-owned commercial banks.